Functional Analysis of AP-2 α and μ2 Subunits - Motley, Alison M. (The American Society for Cell Biology, 2006)
The AP-2 adaptor complex plays a key role in cargo recognition and clathrin-coated vesicle formation at the plasma membrane. To investigate the functions of individual binding sites and domains of the AP-2 complex in vivo, we have stably transfected HeLa cells with wild-type and mutant small interfering RNA–resistant α and μ2 subunits and then used siRNA knockdowns to deplete the endogenous proteins. Mutating the PtdIns(4,5)P2 binding site of α, the phosphorylation site of μ2, or the YXXΦ binding site of μ2 impairs AP-2 function, as assayed by transferrin uptake. In contrast, removing the C-terminal appendage domain of α, or mutating the PtdIns(4,5)P2 binding site of μ2, has no apparent effect. However, adding a C-terminal GFP tag to α renders it completely nonfunctional. These findings demonstrate that there is some functional redundancy in the binding sites of the various AP-2 subunits, because no single mutation totally abolishes function. They also help to explain why GFP-tagged AP-2 never appears to leave the plasma membrane in some live cell imaging studies. Finally, they establish a new model system that can be used both for additional structure-function analyses, and as a way of testing tagged constructs for function in vivo.